Evaluation of the radioprotective action of anserine along with zinc in albino rats exposed to gamma-radiation - Sanaa A. Ali, Lila M. Fadda, Hesham Elebiary, Miada Soliman (Journal of Applied Pharmaceutical Science)
Administration of dietary antioxidants has been suggested to protect against the subsequent liver tissue damage. The present data to explore the hepatoprotective and antioxidant effect of anserine nitrate and /or zinc chloride against γ-irradiation induced hepatotoxicity. Healthy male albino rats were exposed to γ-irradiation from Co60 gamma cell 3500 at dose level (5.7 Gy) at a dose rate 2.67 rad/sec after 24 h and 14 days on the liver and to determine both prophylactic and therapeutic role of intraperitoneally administrated. Exposure to γ- irradiation induced a significant increase in levels of ALP, ALT and AST, while levels of glucose, total proteins, albumin, triglycerides, cholesterol, LDL-C, HDL-C, total, direct and indirect bilirubin and serum fractions were significantly decreased except for total lipids level which was almost not affected. Administration of anserine and/or zinc prior or after radiation exposure was found to offer protection against γ-irradiation induced hepatocellular damage and oxidative stress in rats, probably by exerting a protective effect against hepatocellular necrosis via its free radical scavenging and membrane stabilizing ability.
Keywords: Anserine, Gamma radiation, albumin, protein, lipid profile, liver.